The killing habit - Billingham, Mark (Billingham, Mark. DI Tom Thorne series., 2018)
"From "one of the most consistently entertaining, insightful crime writers working today" (Gillian Flynn), The Killing Habit again brings together favorite wild-card detective Tom Thorne and straight-laced DI Nicola Tanner on a pair of lethally high-stakes cases. While DI Nicola Tanner investigates the deadly spread of a dangerous new drug, Tom Thorne is handed a case that he doesn't take too seriously, until a spate of animal killings points to the work of a serial killer. When the two cases come together in a way that neither could have foreseen, both Thorne and Tanner must risk everything to catch two very different killers"--